Salivary uric acid across child development and associations with weight, height, and body mass index - Riis, J. L.; Dent, A. L.; Silke, O.; Granger, D. A. (Frontiers in Pediatrics, 2023)
Introduction: Obesity during childhood is a serious and growing chronic disease with consequences for lifelong health. In an effort to advance research into the preclinical indicators of pediatric obesity, we examined longitudinal assessments of uric acid concentrations in saliva among a cohort of healthy children from age 6-months to 12-years (n’s per assessment range from 294 to 727). Methods: Using data from a subsample of participants from the Family Life Project (an Environmental influences on Child Health Outcomes Program cohort), we: 1) characterized salivary uric acid (sUA) concentrations from infancy to early adolescence by sex and race; 2) assessed changes in sUA levels across development; and 3) evaluated associations between sUA concentrations and measures of child weight, height, and body mass index (BMI). Across four assessments conducted at 6-, 24-, 90-, and 154-months of age, 2,000 saliva samples were assayed for UA from 781 participants (217 participants had sUA data at all assessments). Results: There were no significant differences in sUA concentrations by sex at any assessment, and differences in sUA concentrations between White and non-White children varied by age. At the 90- and 154-month assessments, sUA concentrations were positively correlated with measures of child weight, height, and BMI (90-month: weight- ρ(610)=0.13, p<0.01; height- ρ(607)=0.10, p<0.05; BMI- ρ(604)=0.13, p<0.01; 154-month: weight- ρ(723)=0.18, p<0.0001; height- ρ(721)=0.10, p<0.01; BMI- ρ(721)=0.17, p<0.0001). Group based trajectory modeling identified two groups of children in our sample with distinct patterns of sUA developmental change. The majority (72%) of participants showed no significant changes in sUA across time (‘Stable’ group), while 28% showed increases in sUA across childhood with steep increases from the 90- to 154-month assessments (‘Increasing’ group). Children in the Increasing group exhibited higher sUA concentrations at all assessments (6-month: t(215)=-5.71, p<0.001; 24-month: t(215)=-2.89, p<0.01; 90-month: t(215)=-3.89, p<0.001; 154-month: t(215)=-19.28, p<0.001) and higher weight at the 24- and 90-month assessments (24-month: t(214)=-2.37, p<0.05; 90-month: t(214)=-2.73, p<0.01). Discussion: Our findings support the potential utility of sUA as a novel, minimally-invasive biomarker that may help advance understanding of the mechanisms underlying obesity as well as further surveillance and monitoring efforts for pediatric obesity on a large-scale.